Stock Management Information System Audit at CV Gudcare Indonesia Corp using COBIT 5 - Nurhayati, Eli; Puspita, Silvy Milda; Putri, Rhizma Elliza; Choirila Vernanda, Isyana Valda; Wulansari, Anita (Sistemasi: Jurnal Sistem Informasi, 2024)
CV Gudcare Indonesia Corp is a company that operates in the fragrance or perfume sector and oversees 2 brands within it. CV Gudcare Indonesia has an information system that is used to carry out stock management. The evaluation was carried out to ensure that the use of information system CV Gudcare Indonesia Corp was running effectively and in line with organizational goals and was able to fulfill the company's vision and mission. Using the COBIT 5 framework subdomains APO10 and APO11, which is useful for measuring the capability level of the performance of the stock management website and knowing how far the process is going. The results of the evaluation that have been carried out show that the capability level gap value produced in the APO10 process is 2, with the Managed Suppliers process at Level 1 (Performed). Meanwhile, in the APO11 domain, the resulting capability level gap value was found to be 2, with the Managed Quality process being at Level 1 (Performed). In future research, more process domains can be added in both the Governance and Management areas, so that evaluations can be carried out more comprehensively.